Absence of haemosporidian parasite infections in the long-lived Cory’s shearwater: evidence from molecular analyses and review of the literature - Campioni, Letizia (2017)
The apparent scarcity or absence of blood parasites in some avian groups, such as seabirds, has been related to intrinsic and extrinsic factors including host immunological capacity, host-parasite assemblage, and ecological parameters, but also to reduced sensitivity of some methods to detect low parasite prevalence/intensities of infection. Here, we examined the haemosporidian parasite prevalence in a breeding population of Cory's shearwater Calonectris diomedea borealis, a long-distance migrant seabird, nesting in the Macaronesian region, in the Eastern Atlantic. Previous studies on Calonectris diomedea complex were based on small sample sizes providing weak evidence for a lack of infections by haemoparasites. Here, we investigated the presence of both parasite infections in C. d. borealis and larvae of potential mosquito vectors on the area. By employing a PCR-based assay, we extensively examined the prevalence of blood parasites belonging to the genera Plasmodium, Haemoproteus, and Leucocytozoon in 286 individuals from different life stages (i.e., chicks, immatures, sabbatical, and breeding adults), facing their specific energetic trade-offs (immunological functions vs. life history activities). We sampled immatures and adult shearwaters, of different sexes, ages, and migratory origins, from two sub-colonies. None of the sampled individuals were infected by these parasites, supporting the hypothesis that there was no in situ or ex situ transmission of vector-borne parasites in marine habitats irrespective of host's life stage and in spite of the presence of the potential Plasmodium vector Culiseta longiareolata breeding in the area. These results suggest that the lack of transmission of haemosporidian parasites on Selvagem Grande may be related to the lack of suitable dipteran vectors at the study sites, which may result from the geographic isolation of this area.